Tollip SNP rs5743899 modulates human airway epithelial responses to rhinovirus infection. Issue 12 (21st September 2016) - Huang, C.; Jiang, D.; Francisco, D.; Berman, R.; Wu, Q.; Ledford, J. G.; Moore, C. M.; Ito, Y.; Stevenson, C.; Munson, D.; Li, L.; Kraft, M.; et al.
Summary: Background: Rhinovirus (RV) infection in asthma induces varying degrees of airway inflammation (e.g. neutrophils), but the underlying mechanisms remain unclear. Objective: The major goal was to determine the role of genetic variation [e.g. single nucleotide polymorphisms (SNPs)] of Toll‐interacting protein (Tollip) in airway epithelial responses to RV in a type 2 cytokine milieu. Methods: DNA from blood of asthmatic and normal subjects was genotyped for Tollip SNP rs5743899 AA, AG and GG genotypes. Human tracheobronchial epithelial (HTBE) cells from donors without lung disease were cultured to determine pro‐inflammatory and antiviral responses to IL‐13 and RV16. Tollip knockout and wild‐type mice were challenged with house dust mite (HDM) and infected with RV1B to determine lung inflammation and antiviral response. Results: Asthmatic subjects carrying the AG or GG genotype (AG/GG) compared with the AA genotype demonstrated greater airflow limitation. HTBE cells with AG/GG expressed less Tollip. Upon IL‐13 and RV16 treatment, cells with AG/GG (vs. AA) produced more IL‐8 and expressed less antiviral genes, which was coupled with increased NF‐κB activity and decreased expression of LC3, a hallmark of the autophagic pathway. Tollip co‐localized and interacted with LC3. Inhibition of autophagy decreased antiviral genes in IL‐13‐ and RV16‐treated cells. Upon HDM and RV1B, Tollip knockout (vs. wild‐type) mice demonstrated higher levels of lung neutrophilic inflammation and viral load, but lower levels of antiviral gene expression. Conclusions and Clinical Relevance: Our data suggest that Tollip SNP rs5743899 may predict varying airway response to RV infection in asthma.